Core/shell polymethyl methacrylate/polyethyleneimine particles incorporating large amounts of iron oxide nanoparticles prepared by emulsifier-free emulsion polymerization - Nuttaporn Pimpha (2018)
A facile synthetic route for the preparation of magnetic poly(methyl methacrylate) (PMMA) core/polyethyleneimine (PEI) shell colloidal particles, possessing high saturation magnetization is reported. Bilayer oleic acid-stabilized iron oxide nanoparticles (bIOs) were designed to have both favorable encapsulation of iron oxide nanoparticles and interaction with protonated amine groups of PEI. The prepared particles had diameter ranging from 180 to 207 nm with narrow size distribution and displayed highly positive surface charges up to +47 mV. TEM revealed that the well-defined bIOs were successfully encapsulated inside the polymer core-shell colloids. Thermogravimetric analysis and magnetization study indicated that these colloidal particles had the magnetic material up to 80 wt % loading and exhibited superparamagnetic property with high saturation magnetization. Thus, they could be potentially useful in various applications, including magnetic separation, medical diagnostics, or drug delivery. © 2012 Elsevier Inc. All rights reserved.